1993
DOI: 10.1177/095632029300400407
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Inhibition of Primary Isolates of Human Immunodeficiency Virus Type 1 by Combinations of 3′-Fluoro-3′-Deoxythymidine and 2′,3′-Dideoxyinosine

Abstract: We examined the antiviral effect against human immunodeficiency virus type 1 of 3'-fluoro-3'-deoxythymidine and 2',3'-dideoXyinQsine, both alone andln combination. Primary isolatia of human immunodeficiency virus were used dlfectly after isolation on peripheral blood mononuclear cells, without culturing on established cell lines, in order to maintain close similarity to the clinical situation. All isolates were synergistically inhibited by combinations of the drugs, though their susceptibility to the separate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

1994
1994
1998
1998

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…REV.specific contributions by residues 181 and 188, and that other regions, in particular the region defined by residues 101 to 106, and a segment located between amino acids 225 and 427 may also be important for specifying drug susceptibility(99,211). Characterization of drug-resistant virus mutants that arise in vitro, upon passage of HIV-1 in the presence of the NNRTIs, revealed that the amino acid residues100,103,106,138,179,181,188,190, and 236 (at either the p66 or the p51 subunit) of HIV-1 RT are crucial in the susceptibility of the virus to the NNRTIs. Amino acid substitutions at these positions invariably lead to resistance of the enzyme and the virus to one or more Also, drug-resistant virus strains emerging upon passage of HIV-1 in the presence of NNRTIs in cell culture may be predictive of the mutations that could arise in the clinic in patients treated with the NNRTIs.…”
mentioning
confidence: 99%
“…REV.specific contributions by residues 181 and 188, and that other regions, in particular the region defined by residues 101 to 106, and a segment located between amino acids 225 and 427 may also be important for specifying drug susceptibility(99,211). Characterization of drug-resistant virus mutants that arise in vitro, upon passage of HIV-1 in the presence of the NNRTIs, revealed that the amino acid residues100,103,106,138,179,181,188,190, and 236 (at either the p66 or the p51 subunit) of HIV-1 RT are crucial in the susceptibility of the virus to the NNRTIs. Amino acid substitutions at these positions invariably lead to resistance of the enzyme and the virus to one or more Also, drug-resistant virus strains emerging upon passage of HIV-1 in the presence of NNRTIs in cell culture may be predictive of the mutations that could arise in the clinic in patients treated with the NNRTIs.…”
mentioning
confidence: 99%
“…Antiviral assays were performed in microtiter plates (5,6,8). Each well contained 50,000 PBMCs, between 10 and 50 times the 50% tissue culture infective dose of the laboratory strain (IIIB) or a primary isolate, and eight serial dilutions in cell culture media containing (i) PFA, (ii) ddI, (iii) ddC, (iv) a 10:1 combination of PFA and ddI, (v) a 1,000:1 combination of PFA and ddC, and (vi) a 100:1 combination of ddI and ddC.…”
mentioning
confidence: 99%